Pharmacokinetics of Cefamandole nafate in a new dosage form - Torres, William Deloso 1943-
Three suppository bases made from mixtures of polyethylene glycols and polyethylene glycol ether were selected for further evaluation when combined with cefamandole nafate powder. Cefamandole nafate (Mandol R, Lilly) is a new parenteral cephalosporin with extended gram-negative in vitro activity. It is active against gram-negative bacilli, gram-positive cocci and some anaerobic organisms. The selected bases were evaluated in vitro as to hardness, friability, uniformity, melting point, stability at selected storage temperatures, and dissolution properties at physiological conditions [37(degrees C) and pH 6.2]. In vitro and in vivo tests were conducted using the vaginal suppositories containing cefamandole nafate. Parous rabbits were used in this experiment. High performance liquid chromatography (HPLC) was used to analyze amounts of cefamandole in dissolution and plasma samples. The pharmacokinetic parameters were determined from the plasma concentrations of cefamandole versus time for each formulation in each rabbit based on a 3x3 Latin square design.